2012
DOI: 10.1159/000341378
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Biased miRNA Expression in Atlantic Halibut <b><i>(Hippoglossus hippoglossus)</i></b> Brain and Gonads

Abstract: The role of miRNA in fish sexual development is not elucidated yet. We profiled miRNAs in gonads and brains of Atlantic halibut using SOLiD sequencing technology. We found tissue- and sexually dimorphic expression of several miRNAs, including miR-29a, miR-34, miR-143, miR-145, miR-202-3p, miR-451, and miR-2188. miR-9 and miR-202 were abundant in brain and gonads, respectively. In the next step, we selected some miRNAs showing differential expression patterns between sexes and performed RT-qPCR on 3 age groups:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
58
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 116 publications
8
58
0
Order By: Relevance
“…38 A growing number of studies showed that miR-202-5p was the evolutionarily conserved gonadal miRNA and has been detected in immature and mature gonads in a few of vertebrate species, including Atlantic halibut, chicken, human, mouse, and Xenopus. 34,[39][40][41][42] To date, no direct physiological function for miR-202-5p has been illustrated. Studies in mammals indicated that miR-202-5p was expressed in a testis-enriched pattern and was downstream of sox9, which is important for male sex determination, suggesting an early role in testisspecific organogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…38 A growing number of studies showed that miR-202-5p was the evolutionarily conserved gonadal miRNA and has been detected in immature and mature gonads in a few of vertebrate species, including Atlantic halibut, chicken, human, mouse, and Xenopus. 34,[39][40][41][42] To date, no direct physiological function for miR-202-5p has been illustrated. Studies in mammals indicated that miR-202-5p was expressed in a testis-enriched pattern and was downstream of sox9, which is important for male sex determination, suggesting an early role in testisspecific organogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Atlantic Halibut ( Hippoglossus hippoglossus ), a fish with an XY sex-determining system, also has a considerable enrichment of piRNAs in ovary compared with that in testis by SOLiD sequencing. However, there is no obvious typical miRNA peak in gonad of Atlantic Halibut [34], [35]. In the miRNA transcriptome of Nile Tilapia by Solexa sequencing, there are both typical miRNA and piRNA peaks [36].…”
Section: Discussionmentioning
confidence: 99%
“…Each of these sex-biased miRNAs exhibited sex-biased expression in adults, but sex-biased miRNA expression was lower in pre-adults (with 5% and 4% of the total miRNAs being sex biased in larvae and pupae, respectively). Genome-wide sex biases in miRNA expression have also been identified in zebra finches (Luo et al 2012), silkworm (Liu et al 2010), schistosomes (Marco et al 2013), and halibut brain and gonad tissue (Bizuayehu et al 2012). In halibut, patterns of sex-biased expression suggest a role of miRNAs in sexual development.…”
Section: Sex-biased Gene Expression and Sexual Conflictmentioning
confidence: 98%
“…These miRNAs target mRNAs with complementary sequences and bind to them to regulate their expression, potentially by tagging the mRNA for destruction, or by preventing their translation (Pasquinelli 2002). Relatively little is known about sex-biased expression of miRNAs, although RNA-sequencing in the zebra finch, Taeniopygia guttata, has found genome-wide sex-biased expression of some miRNAs (Luo et al 2012), and patterns of sex-biased miRNA expression have also been found in halibut (Bizuayehu et al 2012), silkworm (Liu et al 2010), and schistosomes (Marco et al 2013). Taken together with the evidence for sex-biased miRNA expression in D. melanogaster from our unpublished data described below, it seems that further research on the sex-specific functions of miRNAs could shed some light on the mechanisms that control sex-biased gene expression.…”
Section: Sex-biased Gene Regulation and Evolutionmentioning
confidence: 99%